The international labour migration and productivity of national economy - Metelyov, S. Y. (Univerzita Pardubice, 2007)
A role and problems of formation of processes of the international migration in the advanced counntries in modern conditions are opened; the special importance for increase of productivity of the Russian economy in long-term prospect of attraction of labour immigrants is proved within the limits of immigration capacity of the country.

A role and problems of formation of processes of the international migration in the advanced counntries in modern conditions are opened; the special importance for increase of productivity of the Russian economy in long-term prospect of attraction of labour immigrants is proved within the limits of immigration capacity of the country.
Keywords: Trh práce; Rusko; produktivita ekonomiky; stěhování za prací; mezinárodní trhy